MXene: A wonderful nanomaterial in antibacterial - Ye, Surong; Zhang, Huichao; Lai, Huiyan; Xu, Jingyu; Yu, Ling; Ye, Zitong; Yang, Luyi (Frontiers in Bioengineering and Biotechnology, 2024)
Increasing bacterial infections and growing resistance to available drugs pose a serious threat to human health and the environment. Although antibiotics are crucial in fighting bacterial infections, their excessive use not only weakens our immune system but also contributes to bacterial resistance. These negative effects have caused doctors to be troubled by the clinical application of antibiotics.Facing this challenge, it is urgent to explore a new antibacterial strategy. MXene has been extensively reported in tumor therapy and biosensors due to its wonderful performance. Due to its large specific surface area, remarkable chemical stability, hydrophilicity, wide interlayer spacing, and excellent adsorption and reduction ability, it has shown wonderful potential for biopharmaceutical applications. However, there are few antimicrobial evaluations on MXene. The current antimicrobial mechanisms of MXene mainly include physical damage, induced oxidative stress, and photothermal and photodynamic therapy. In this paper, we reviewed MXene-based antimicrobial composites and discussed the application of MXene in bacterial infections to guide further research in the antimicrobial field.